2009
DOI: 10.1159/000218526
|View full text |Cite
|
Sign up to set email alerts
|

ProACT™ for Stress Urinary Incontinence after Radical Prostatectomy

Abstract: Introduction: Stress urinary incontinence is a bothersome complication of radical prostatectomy. Surgical treatment consists of the artificial urinary sphincter (AUS), the male sling and bulk injections. This study presents the results of the first series of implantations of ProACTTM in the Netherlands. Materials and Methods: A non-validated questionnaire was sent to 29 male patients implanted with ProACT to determine Stamey score, pad count and questions about quality of life and satisfaction. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
1
5
0
1
Order By: Relevance
“…Using similar definitions to those in this study, dry rates between 31 and 81% have been reported with ProACT [4][5][6]9]. Thus, the dry rate in this study is lower than that found in some other studies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Using similar definitions to those in this study, dry rates between 31 and 81% have been reported with ProACT [4][5][6]9]. Thus, the dry rate in this study is lower than that found in some other studies.…”
Section: Discussionsupporting
confidence: 83%
“…One of the most recent treatments, which has the advantage of being minimally invasive, is the insertion of adjustable continence balloons, ProACT (ProACT Ô , Uromedica, Plymouth, USA), as first described by Hübner and Schlarp in 2005 [4]. These operations have shown promising results [5][6][7][8][9]. The objective of this article is to evaluate the results of the Danish experience with ProACT.…”
Section: Introductionmentioning
confidence: 99%
“…The 32.4% rate of revision surgery in this cohort is standard when compared to published literature with comparable length of follow‐up. Noordhoff et al (46 mos), Martens et al (41 mos), and Roupert et al (56.3 mos) show revision rates of 30.1%, 41.3%, and 13.3%, respectively. This revision rate is also similar to what has been published in the artificial urinary sphincter literature …”
Section: Discussionmentioning
confidence: 95%
“…Cette technique est encore en cours d'évaluation, avec, à ce jour, neuf séries publiées concernant 441 patients [4][5][6][7][8][9][10][11][12].…”
Section: Abstract Sphincteral Insufficiency · Periurethral Balloonsunclassified
“…The average age at the time of implantation was 68.78 years . The average waiting time between RP and implantation was 4.04 years [0][1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. The average number of daily protections prior to treatment was 2.3 (/47 patients) [0 condom catheter].…”
mentioning
confidence: 99%